Introduction to Transport Phenomena Modeling A Multiphysics, General Equation-Based Approach - Ruocco, Gianpaolo (Springer International Publishing, 2018)
This text offers an introduction to multiple transport phenomena as they occur in various fields of physics and technology like transport of momentum, heat, and matter. These phenomena are found in a number of physical processes in the fields of chemical, food, biomedical, and environmental biotechnology. The book puts a special emphasis on modeling both purely diffusive mechanisms and macroscopic transport such as heat and mass convection and Navier-Stokes equations.To allow the best applicability of the various concepts, they are presented with a synthesis of simplicity of exposure with respect to completeness. The book includes more than 80 graphs and figures, to facilitate the understanding of the various topics. It also presents many examples will be made throughout the text. To control that the learned materials is properly understood various exercises are included.